Arabic Learning with Problem-Based Learning Models and PowerPoint Media in Improving Students' Interest - Ulin Nuha, Muhammad Afthon; Musyafaah, Nurul (Arabi : Journal of Arabic Studies, 2023)
The aims of this study were (1) to explore out the process of implementing Problem Based Learning using PowerPoint media in Arabic lessons at MA Fattah Hasyim Tambakberas Jombang; (2) To find out the results of applying Problem Based Learning in Arabic lessons with PowerPoint media in increasing student learning interest. This research method uses a descriptive qualitative approach, with data collection techniques using observation, interviews, and documentation. The data analysis technique uses data reduction, data presentation, and conclusion and verification. The results of the study show (1) The implementation of the Problem Based Learning model at MA Fattah Hasyim Tambakberas Jombang in Arabic for class XI is carried out through three stages, namely the preparation stage, the implementation stage, and the evaluation stage. (2) Overall, it can be concluded that student's interest in learning Arabic using the Problem Based Learning model is included in the outstanding category; this is because students can explore further problems that are closely related to student's daily lives and also required to be able to think critically and cooperate in groups to solve the problems presented in learning.